1983
DOI: 10.1021/ic00162a019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal reactions of metal complexes under quasi-isothermal and -isobaric conditions. 3. Solid-phase thermal reactions of the doubly complexed salts of the forms [(Cr or Co)(NH3)6][(Cr or Co)(CN)6], [(Cr or Co)(H2O)(NH3)5][(Cr or Co)(CN)6], and cis-[(Co(H2O)2(NH3)4][Co(CN)6]

Abstract: Durch Reaktion der [Hexammin‐ bzw. Aquopentammin‐metall(III)]‐nitrate oder ‐chloride mit K‐hexacyanocobaltat(III) bzw. ‐chromat(III) wurden die neun Titelkomplexe dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This is not an unlikely event, because CN ligand flipping upon heating has been previously reported in Prussian blue, 14,25 its analogues, 26,39 and other CNcontaining transition-metal complexes. 27 In the present work, we have not evaluated whether the cyanide ligand inversion is caused by a flip or an alternative mechanism.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is not an unlikely event, because CN ligand flipping upon heating has been previously reported in Prussian blue, 14,25 its analogues, 26,39 and other CNcontaining transition-metal complexes. 27 In the present work, we have not evaluated whether the cyanide ligand inversion is caused by a flip or an alternative mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…It has been previously reported that an increased temperature can lead to “cyanide flipping” in the bridged complexes, , and this may play a role in the reduction processes. It has also been observed that the temperature of reduction is affected by the chemical environment of the cyanide; bridging cyanide ligands reduce metal centers at lower temperatures than the corresponding terminal cyanides. , The above-mentioned features of the cyanometalate chemistry imply that the coordination chemistry of cyanide-containing compounds at elevated temperature is quite distinctive from the relatively well-understood chemistry of these compounds at room temperature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…After the second inflection point (280 °C) a very pronounced peak at 2194 cm -1 is seen in the high-frequency region (Figure c) along with the further shift of two peaks in the low-frequency region to 534 and 451 cm -1 which we tentatively ascribe to the stretching vibration and bending modes of cyanide ligands ,, in Co(CN) n ( n < 6). It is also possible that these transitions are due to the to formation of KPdCo(CN) 6 compounds, or to formation of Pd(CN) 2 formed by the “flipping” of the cyanide bridges to form Co−NC−Pd bridges.
5 High-frequency transmittance FTIR spectra of 60 mM, Pd/Co = 2/1 xerogel samples, which were taken along the main TG inflection points, run under oxygen, at (a) 150, (b) 240, (c) 280, (d) 420, (e) 650, and (f) 795 °C.
6 Low-frequency transmittance FTIR spectra of 60 mM, Pd/Co = 2/1 xerogel samples, which were taken along the main TG inflection points, run under oxygen, at (a) 150, (b) 240, (c) 280, (d) 420, (e) 650, and (f) 795 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…After the second inflection point (280 °C) a very pronounced peak at 2194 cm -1 is seen in the high-frequency region (Figure 5c) along with the further shift of two peaks in the low-frequency region to 534 and 451 cm -1 which we tentatively ascribe to the stretching vibration and bending modes of cyanide ligands 23,28,29 in Co(CN) n (n < 6). It is also possible that these transitions are due to the to formation of KPdCo-(CN) 6 compounds, or to formation of Pd(CN) 2 formed by the "flipping" of the cyanide bridges [30][31][32][33] to form Co-NC-Pd bridges. Passing through the third mass loss under an oxygen atmosphere at 500 °C (and 650 °C under an argon atmosphere) removes all high-wavenumber vibrations (Figures 4b and 5e,f).…”
Section: Resultsmentioning
confidence: 99%